O espaço doméstico dos quintais e a conservação de plantas medicinais na comunidade São João da Várzea, Mossoró-RN - Freitas, Ana Valeria Lacerda (2016)
The purpose of the present study was to conduct an ethnobotanical research about the use and handling of vegetable resources, especially medicinal, in São João da Várzea s community, Mossoró-RN, emphasizing informants perception in relation to domestic spaces and conservation of these resources. The research was divided in three chapters. First chapter refers to a general introduction and a literature review about the subject. The second chapter includes the study about the use and handling of vegetable resources present in domestic spaces of 22 productive units, emphasizing medicinal plants. The third chapter, on the other hand, includes a study realized with two key informants, in order to recover the traditional knowledge of these about the use and handling of medicinal plants and their perception about phenological aspects and species conservation. The data of the last two chapters were collected using several techniques, such as: direct and participant observation, informal and semistructured interviews, free list, history of life, participative mapping and guided tour or walk-in-the-woods. The domestic spaces of productive units realized by the 22 informants have own characteristics and functions, modeled in accordance with knowledge and particularity of each family. These spaces are consisting of a large diversity of vegetable species that being used for many purposes, especially the medicinal use. The two key informants show to have a lot of knowledge about medicinal use of species found in domestic spaces and around the productive units, as well as about phenological aspects, handle and conservation of them